Differential susceptibility to chromatid breaks induced by bleomycin in sub-fertile and fertile bovines - Luna, H. S.; Ferrari, I; Luna, H.; McManus, C.; Padovani, C. R.; Rumpf, R. (Elsevier B.V., 2004)
The rate of chromatid breaks was studied in cows with a history of sub-fertility by means of a test based on measurement of the average of breaks induced in lymphocytes of peripheral blood cultures. Fourteen female specimens were divided into two groups: fertile and sub-fertile. Peripheral blood lymphocytes were cultured and prepared for cytogenetic analysis. Two types of culture were established for each animal to evaluate the response of peripheral blood lymphocyte cultures to the genotoxic effects of bleomycin. The first culture did not receive bleomycin treatment (spontaneous chromosome aberrations). Our results showed that median breaks per cell (b/c) (+/-semirange) for spontaneous culture of the fertile and sub-fertile animals and bleomycin sensitivity assay for fertile and sub-fertile animals were 0.00 +/- 0.06, 0.02 +/- 0.03, 0.08 +/- 0.05 and 0.22 +/- 0.09, respectively. There was no significant difference (P > 0.05) in the chromosomal breakage in lymphocytes not exposed to bleomycin; however, in comparing the number of chromatid breaks per cell in cultures treated with bleomycin, the sub-fertile group showed a significantly higher (P < 0.05) level than the fertile group. These findings have implications both for identifying cattle with less than optimum fertility as well as for providing potential avenues to study the origins of sub-fertility. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: bleomycin; bovine; chromatid breaks; fertility; sub-fertility